Deep Learning Approach in Teaching Angles at Muhammadiyah Elementary School 2 Banda Aceh - Fitriyasni Fitriyasni (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2025)
This study aims to analyze the implementation of a deep learning approach in mathematics education focusing on angle material at Muhammadiyah Elementary School 2 Banda Aceh. The study uses a descriptive qualitative method involving 18 students and a mathematics teacher. Data were collected through observation, interviews, and documentation. Findings show that the deep learning approach helps students understand the concept of angles deeply through mindful, meaningful, and joyful activities. Supporting factors include student engagement, instructional tools, and teacher guidance, while limiting factors include time constraints and lack of teacher training.Keywords: deep learning, mathematics learning, angles, elementary school